Correlation of OPG/RANKL in Patients with Thalassemia Major in the Center of Haemoglobinopathy Lushnje, Albania - Zoga, Jorida; Kallco, Majlinda; Refatllari, Etleva (European Scientific Journal, ESJ, 2024)
Osteoporosis is an important cause of morbidity in hemoglobinopathy patients. It is characterized by low bone mass and disruption of bone architecture, resulting in reduced bone strength and increased risk of fractures. Osteoprotegerin (OPG) and receptor activator of NF-kappa-B ligand (RANKL) have been recently implicated in the pathogenesis of various types of osteoporosis. The aim of our study was to determine if there was any correlation between OPG/RANKL and the patients affected by thalassemia major in the Center of Haemoglobinopathy in Lushnje. Methods: We measured in 70 patients with Thalassemia major and in 67 healthy control serum OPG and RANKL levels and determined correlations with BMD. We measured T-score and BMD too. Results: 31.1% of our patients with Thalassemia major had osteoporosis and 21.6 % had osteopenia. We found a correlation between OPG-BMD (r=-0.768, p=0.000 and RANKL-BMD (r=0.468; p=0.000). OPG-T-score (r=0.729. p=0.000) and Rankl-T-score r=-0.409; p=0.000). Conclusion: OPG and RANKL in Thalassemia major patients should be consider as a main factor responsible for osteoclast activation.